Parents reported oral sensory sensitivity processing and food preference in ADHD. Issue 5 (6th October 2011) - GHANIZADEH, A.
Abstract : Accessible summary: Oral sensory overresponsivity is frequently seen in attention deficit hyperactivity disorder (ADHD) children with oppositional behaviours. Attention deficit hyperactivity disorder children with oppositional behaviours are more likely to adhere to the same foods. Food preferences in ADHD children co‐morbid with oppositional behaviour are more common than in those without oppositional behaviours. Children with both ADHD and oppositional behaviours are less likely to try new food and have limited repertoire of foods. Behavioural and food recommendation for children with ADHD should consider their co‐morbid behaviours. Abstract: Oral sensory processing in children with attention deficit hyperactivity disorder (ADHD) is an area with limited research. Oppositional defiant disorder (ODD) and separation anxiety disorder (SAD) symptoms usually co‐occur with ADHD. This study investigates the association of oral sensory processing problems with ODD and SAD symptoms in children with ADHD. The parents of 189 children with ADHD completed Oral Over‐ and Underresponsivity Behaviors Inventory reporting oral overresponsivity (OR) and underresponsivity (UR) of their children. Only ODD score predicted OR scale score. None of ADHD severity, anxiety score, age and gender predicted OR score. UR scale score was only predicted by SAD and inattention scores. ODD score and hyperactivity/impulsivity score did not predict UR score. The ODD behaviour in children with ADHD needs to be evaluated and managed more extensively and it should include oral sensory occupational therapy. Future studies should extend this research to children with ADHD and obesity and food reward system.